2011
DOI: 10.1080/01634372.2011.595476
|View full text |Cite
|
Sign up to set email alerts
|

Health and Medical Services Use: A Matched Case Comparison Between CCRC Residents and National Health and Retirement Study Samples

Abstract: Little is known about the health status of adults living in continuing care retirement communities (CCRC). Using matched-case control, 458 adults from the Health and Retirement Study (HRS) or a CCRC-based sample were compared on total comorbidity, self-rated health, home health services use, and hospitalizations. At year 2, the CCRC sample reported more comorbidities (96%) but significantly better self-rated health (96% good/excellent) than the HRS sample (93% comorbidity, 73% good/excellent; p < .01). There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 13 publications
(13 reference statements)
2
17
0
Order By: Relevance
“…Instrumental activities of daily living (IADL) included ability to use the phone, shopping, preparing for food, responsibility for own medications, and ability to handle finances. The number of limitations in instrumental activities of daily living (IADL) was the sum of any difficulties on these five tasks [ 21 , 24 ]. Limitations in mobility included difficulty in any of the following tasks such as walking one block, walking several blocks, waking across a room, climbing one flight of stairs, and climbing several flights of stairs.…”
Section: Methodsmentioning
confidence: 99%
“…Instrumental activities of daily living (IADL) included ability to use the phone, shopping, preparing for food, responsibility for own medications, and ability to handle finances. The number of limitations in instrumental activities of daily living (IADL) was the sum of any difficulties on these five tasks [ 21 , 24 ]. Limitations in mobility included difficulty in any of the following tasks such as walking one block, walking several blocks, waking across a room, climbing one flight of stairs, and climbing several flights of stairs.…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of chronic illness among older Americans suggests a high burden of disease and functional impairment in later life. About 80% of older adults have one chronic condition, and 68% have two or more chronic conditions (Centers for Disease Control, 2013), and this may be higher for older adults living in retirement communities (Gaines, Poey, Marx, Parrish, & Resnick, 2011). A recent study found that impairments in functional health, depression, and memory problems were significantly related to worse QoL among older people in the United States (Baernholdt, Hinton, Yan, Rose, & Mattos, 2012).…”
mentioning
confidence: 99%
“…They found that CCRC residents were at less risk for activities of daily living (ADL) limitations and had better self-reported health two years after baseline measure. Gaines et al (2011) obtained similar results when comparing CCRC residents to community-dwelling older adults from the US Health and Retirement Study (HRS). They found that at follow-up two years later, CCRC residents reported more comorbidities, while having better subjective health.…”
Section: Introductionmentioning
confidence: 80%
“…Gaines et al . (2011) compared CCRC-based or community-based older adults from the HRS, and found no difference in objective health between residents and non-residents. They found, however, better subjective health among CCRC residents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation